A decade of shaking in the Garden City: the dynamics of preparedness, perceptions, and beliefs in Canterbury, New Zealand, and implications for earthquake information - Becker JS; Vinnell LJ; Doyle EEH; McBride SK; Paton D; Johnston DM (Frontiers Media S.A., 2024)
Introduction: This study explored earthquake preparedness over time—before, during, and 10 years after the Canterbury Earthquake Sequence (CES) in New Zealand (NZ; known as Aotearoa in te ao Māori). Method: Surveys of Canterbury residents were conducted in 2009, 2013, and 2021, using variables derived from Community Engagement Theory (CET). The surveys measured earthquake perceptions and beliefs, participation and engagement, and preparedness actions. Results were compared across the three samples. Results: Findings indicate that perceptions and beliefs (e.g., risk perception, outcome expectancy beliefs), and types of preparedness actions taken (e.g., collection of survival items, structural preparedness, community and/or agency relationships), differed over time, depending on people's experiences before, during, and after the CES. For example, during and after the CES, people were more likely to believe that preparing provided a benefit to daily life, but less likely to think it could reduce property damage, perhaps due to people's experiences of disruption and damage during the earthquakes. Discussion: An understanding of such dynamics can assist with the provision and timing of risk and preparedness information. This study highlights the importance of providing applicable and actionable preparedness information, that is relevant to people's experiences, throughout an earthquake sequence. Such information might evolve and change in focus over time depending on risks and needs. Focus could also be given to information that builds peoples beliefs and capacities to undertake preparedness in evolving situations. Understanding preparedness in the context of different experiences and timeframes is useful in helping update models such as the CET, where the dynamics of time might be better incorporated.
Keywords: preparedness; readiness; earthquakes; Christchurch; Canterbury; New Zealand